1997
DOI: 10.1076/ceyr.16.2.127.5089
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycan synthesis and its expression are decreased in the retina of diabetic rats

Abstract: The decrease in HSPG synthesis may account for the reported decrease in retinal basement membrane anionic sites and increased capillary permeability that occurs in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 25 publications
0
16
1
3
Order By: Relevance
“…High glucose levels upregulate cell-associated proteoglycans in retinal pericytes 58 and promote the secretion of HS chains by endothelial cells, 59 and VEGF increases the retinal expression of the HS side chains of HSPGs. 60 Perlecan binds FGFs, 61,62 and the intraretinal stores of immunoreactive bFGF and HSPG increase in patients with DR. 63 Of note, abnormal HSPG expression and structure can contribute to vascular leakage and to the release of pro-angiogenic factors in DR, 64 whereas bFGF, αvβ5 integrin, and HGF can signal to promote angiogenesis in DR. 65 However, contrary to what is expected from our findings using rats after 6 weeks of STZ, the mRNA levels of perlecan, the [ 35 S] sulfate incorporation into HSPG, 66 and the immunolocalization of HSPG 67 decrease in the retina of diabetic rats at 5 and 11 months after STZ treatment, respectively. These findings suggest that the synthesis of HSPG may change as diabetes progresses and emphasize the need to examine the long-term differential efficacy of AAV2 vectors.…”
Section: Aav2 Vectors Reverse Diabetic Retinal Alterations N Díaz-lezcontrasting
confidence: 55%
“…High glucose levels upregulate cell-associated proteoglycans in retinal pericytes 58 and promote the secretion of HS chains by endothelial cells, 59 and VEGF increases the retinal expression of the HS side chains of HSPGs. 60 Perlecan binds FGFs, 61,62 and the intraretinal stores of immunoreactive bFGF and HSPG increase in patients with DR. 63 Of note, abnormal HSPG expression and structure can contribute to vascular leakage and to the release of pro-angiogenic factors in DR, 64 whereas bFGF, αvβ5 integrin, and HGF can signal to promote angiogenesis in DR. 65 However, contrary to what is expected from our findings using rats after 6 weeks of STZ, the mRNA levels of perlecan, the [ 35 S] sulfate incorporation into HSPG, 66 and the immunolocalization of HSPG 67 decrease in the retina of diabetic rats at 5 and 11 months after STZ treatment, respectively. These findings suggest that the synthesis of HSPG may change as diabetes progresses and emphasize the need to examine the long-term differential efficacy of AAV2 vectors.…”
Section: Aav2 Vectors Reverse Diabetic Retinal Alterations N Díaz-lezcontrasting
confidence: 55%
“…It has been demonstrated that perlecan core protein is downregulated in the liver of diabetic patients (24). In the retinal basement membrane of diabetic patients, a diminished or unaltered perlecan expression has been reported (25,26). Thus far, no report exists about the expression of perlecan in the kidney of humans or animals with diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…Decreased HSPG in DM has been studied predominantly in the context of diabetic nephropathy, although it has been observed in a variety of tissues (82)(83)(84). Decreased expression of perlecan, specifically, has been described in a variety of renal models (85,86).…”
Section: Figurementioning
confidence: 99%